"Carrying the black pot": Food safety and risk in China's reactive regulatory state. Issue 2 (4th May 2022) - Wang, Li; Demeritt, David; Rothstein, Henry
Abstract: This paper explores the struggles of China's party‐state to address chronic food safety problems by adopting international best practices of risk‐based regulation. Despite formally adopting risk‐based approaches for targeting inspections and enforcement in 2002, implementation has been halting and uneven, as we show in the first analysis of risk‐based regulation beyond its OECD heartlands. Drawing on policy document analysis and 36 key informant interviews with food business operators and government officials working on food safety regulation at every level of the state, we identify contradictions between official commitments to risk‐based inspection and top‐down demands for zero tolerance and strict accountability, which leave local inspectors preoccupied with avoiding blame more than reducing safety risks. Our analysis advances recent scholarship on regulatory states of the global South by highlighting how risk‐based ideas, instruments, and practices are refracted through the distinctive norms and style of China's reactive regulatory state.